Progress in gasless endoscopic thyroidectomy - Cheng, Xianbin; Ding, Xiangfu; Wang, Sijia; Li, Siyu; Zhang, Hong (Frontiers in Endocrinology, 2024)
Gasless endoscopic thyroidectomy obviates the necessity for carbon dioxide insufflation to establish a surgical workspace, thus mitigating the potential complications associated with this practice. This technique presents several benefits, such as the maintenance of neck functionality, minimal scarring, and enhanced visibility of the surgical field, which contribute to its extensive adoption in clinical settings. The objective of this study is to synthesize the current methodologies of gasless endoscopic thyroidectomy and to evaluate the advantages and disadvantages inherent to each technique. It aims to offer theoretical insights to assist surgeons in determining the most suitable approach for gasless endoscopic thyroidectomy in their clinical practice.